Pressures on seeding lines influencing cotton emergence and initial growth - Fabian, Wesley Ângelo; Lima, Sebastião Ferreira de; Alves, Edson Rafael; Alves, Vitória Carolina Dantas; Contardi, Lucymara Merquides; Vendruscolo, Eduardo Pradi; Nunes, Rita de Cássia Barros; Cordeiro, Meire Aparecida Silvestrini (Revista de Ciências Agroveterinárias, 2024)
The sowing process is of fundamental importance for the establishment of the crop in the field, and the force applied to the seeding unit is relevant, as it can delay the emergence of cotton seedlings, resulting in a decrease in the development and productive potential of the crop. Thus, the work aimed to evaluate the effect of different pressures exerted on cotton sowing lines on the emergence and initial growth of plants. A randomized block design was used with eight treatments and three replications, totaling 24 plots. The treatments consisted of pressures, manual 16 kg, 45 kg, and 120 kg, light automatic, standard and heavy, customized automatic 36 kg and 59 kg, where each seeding unit had a DeltaForce hydraulic pressure mechanism from the Precision Planting brand. Seedling emergence was evaluated on the 5th, 6th, 7th, and 8th day after sowing, the total number of plants that emerged on the 8th day, the number of exposed seeds, plant height on 20 and 25 days after sowing, and main root length with 15 days after sowing. In the fastest emergence, 5 days after sowing, the 16 and 45 kg manual pressure system obtained a greater number of emerged plants, surpassing the equipment's standard automatic system by 44.6%, however, the use of 16 kg also resulted in a greater number of exposed seeds. The use of automatic pressure system during sowing was not favorable to the emergence of cotton seedlings, with manual systems being more appropriate. There was no difference in plant height 25 days after sowing and root length 15 days after sowing, about the different pressure systems used.